Bruton Tyrosine Kinase Inhibition Attenuates Liver Damage in a Mouse Warm Ischemia and Reperfusion Model. Issue 2 (February 2017) - Palumbo, Tiziana; Nakamura, Kojiro; Lassman, Charles; Kidani, Yoko; Bensinger, Steven J.; Busuttil, Ronald; Kupiec-Weglinski, Jerzy; Zarrinpar, Ali
Abstract : Background: Bruton tyrosine kinase (Btk) is a central player in multiple signaling pathways of lymphoid and myeloid cells. Myeloid cells are crucial early effectors in organ ischemia-reperfusion (IR) injury. BTKB66 is a selective, irreversible inhibitor of Btk. In this study, we hypothesized that Btk inhibition would reduce hepatocellular injury in a murine model of liver warm hepatic IR. Methods: First, BTKB66 was tested in in vitro models of lipopolysaccharide-mediated neutrophil and macrophage activation. Then, to assess its efficacy in vivo, BTKB66 was administered orally to mice for 7 days before subjecting them to 90 minutes of warm hepatic ischemia followed by reperfusion for 6 or 24 hours. Clinical and pathologic features in the livers, including AST, ALT, and a panel of cytokines and chemokines, were examined. Results: BTKB66 potently inhibited lipopolysaccharide-mediated activation of bone marrow–derived neutrophils and macrophages in vitro. It also reduced the severity of IR injury as determined by AST and ALT levels, as well as immune cell infiltrates. BTKB66 significantly decreased hepatic markers of sterile inflammation, such as C-X-C motif chemokine 1, C-X-C motif chemokine 2, and C-X-C motif chemokine 10, in parallel with depression of serum markers of the myeloid cell activation, such as CCL5, CCL11, and C-X-C motif chemokine 5. Conclusions: BTKB66 treatment ameliorated hepatocellular injury in a well-established model of liver partial warm ischemia and in situ reperfusion. These findings confirm that neutrophil recruitment and activation play an essential role in IR stress, and that targeting Btk activity may provide a useful approach for preventing hepatocellular damage and improving outcomes in liver transplantation. Abstract : The authors investigate the protective role of BTKB66, an inhibitor of Bruton's tyrosine kinase (BTK), on hepatic ischemia reperfusion injury both in vitro and in vivo. It suggests that BTK66 attenuates acute phase inflammation by inhibiting neutrophil recruitment and macrophage activation.